2013
DOI: 10.1016/j.regsciurbeco.2012.06.008
|View full text |Cite
|
Sign up to set email alerts
|

The employment cycles of neighboring cities

Abstract: This paper examines the spatial interaction of neighboring cities over their employment cycles. The cycles of neighboring cities tend to be more similar to one another than are those of non-neighboring cities, although this is due primarily to neighbors' tendency to be in the same state. In addition to these same-state effects, neighborness interacts with industry and human capital in ways that make the cyclical interaction of neighbors different from that of non-neighbors. Specifically, neighboring cities wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Industrial structure, represented by employment shares of different industries, is shown to have effects on recession growth rates, and the education level of labour is related to expansion growth rates. Wall (2013) found that neighbouring cities in the U.S. interact over employment cycles, with similar employment cycles for the cities in the same state and with different employment cycles for nearby cities. The author attributed the latter to the tendency of cities in the same metropolitan area to be functionally specialised in industries according to their human capital.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Industrial structure, represented by employment shares of different industries, is shown to have effects on recession growth rates, and the education level of labour is related to expansion growth rates. Wall (2013) found that neighbouring cities in the U.S. interact over employment cycles, with similar employment cycles for the cities in the same state and with different employment cycles for nearby cities. The author attributed the latter to the tendency of cities in the same metropolitan area to be functionally specialised in industries according to their human capital.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The existing literature mainly studies the characteristics of human capital from enterprises and individuals. Wall (2013) believes that the education level of labor force is the key factor to determine a company's acceptance of new technology. [4] Hill (2012) thinks that the reason why many enterprises can't recover to the original level of development after experiencing a big external shock is the massive loss of labor force.…”
Section: Literature Reviewmentioning
confidence: 99%
“…WZ estimated UK regional Beveridge curves using county-level data and the identifying restriction that the slopes of Beveridge curves for counties in the same region are identical and shifts of the Beveridge curve within a region are common.WZ choose their regions exogenously (defined by the government) and to be geographically continuous. For the UK, geographic regions might be justified; however, proximity between MSAs in the U.S. does not necessarily guarantee similarity in the labor markets [see Wall (2013)]. Thus, the assumption of a common slope coefficient across proximate MSAs may be too strong.…”
Section: Regional Beveridge Curvesmentioning
confidence: 99%
“…1 U.S., these types of restrictions may not be optimal as geographic proximity does not guarantee that cities or states will have similar business cycle characteristics [see Owyang, Piger, and Wall (2005); Owyang, Piger, Wall, and Wheeler (2008); and Wall (2013)].…”
Section: Introductionmentioning
confidence: 99%